Case Report: Next-Generation Sequencing Identified a Novel Pair of Compound-Heterozygous Mutations of LPL Gene Causing Lipoprotein Lipase Deficiency - Li, Yakun; Hu, Man; Han, Lin; Feng, Lifang; Yang, Luhong; Chen, Xiaoqian; Du, Tingting; Yao, Hui; Chen, Xiaohong (Frontiers in Genetics, 2022)
Lipoprotein lipase deficiency (LPLD) is a rare disease characterized by accumulation of chylomicronemia with early-onset. Common symptoms are abdominal pain, hepatosplenomegaly, eruptive xanthomas and lipemia retinalis. Serious complications include acute pancreatitis. Gene LPL is one of causative factors of LPLD. Here, we report our experience on an asymptomatic 3.5-month-old Chinese girl with only milky blood. Whole-exome sequencing was performed and identified a pair of compound-heterozygous mutations in LPL gene, c.862G>A (p.A288T) and c.461A>G (p.H154R). Both variants are predicted ‘deleterious’ and classified as ‘likely pathogenic’. This study expanded the LPL mutation spectrum of disease LPLD, thereby offering valuable experience on early diagnosis and proper medication of LPLD.